2015
DOI: 10.1371/journal.pone.0123383
|View full text |Cite
|
Sign up to set email alerts
|

Health and Economic Outcomes of Introducing the New MenB Vaccine (Bexsero) into the Italian Routine Infant Immunisation Programme

Abstract: IntroductionIn January 2013 a novel type of multicomponent protein-based vaccine against group B meningococcal disease was licensed by the European Medicines Agency. With the widespread use of the meningococcal serogroup C conjugate vaccines, serogroup B remains now the major cause of bacterial meningitis and septicaemia in young children in Europe. The aim of this study is to investigate the health and the economic outcomes of MenB vaccine introduction into the Italian routine mass vaccination programme.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 70 publications
(101 reference statements)
0
46
0
1
Order By: Relevance
“…We believe that this approach is one of the strengths of our study. Indeed, cost-effectiveness studies often neglect the issue of underestimation and tend to be very conservative 25-29 . Our study indicated that the parameter “probability of sequelae” was one of the parameters impacting ICER.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…We believe that this approach is one of the strengths of our study. Indeed, cost-effectiveness studies often neglect the issue of underestimation and tend to be very conservative 25-29 . Our study indicated that the parameter “probability of sequelae” was one of the parameters impacting ICER.…”
Section: Discussionmentioning
confidence: 75%
“…Furthermore, a recent Italian cost-effectiveness analysis found that routine infant immunization with Bexsero® would not be cost-effective with an ICER of > 350,000 €/QALY 25 . In this latter study, Tirani et al 25 .…”
Section: Discussionmentioning
confidence: 81%
“…More substantial reductions in disease (71%) can be achieved after 10 years by routinely vaccinating infants in combination with a large-scale catch-up campaign targeting carriage, achieving cost-effectiveness at £17 per vaccine dose. Moreover, data from the Italian Health Service perspective came to the same conclusion evaluating the current incidence levels in Italy and the vaccine price [65]. However as MID incidence varies across the world, further pharmacoeconomic studies in different geographic and sociodemographic settings, including other aspects as parents demand, prevention of outbreak, new marketing strategy are needed to carefully evaluate the introduction of the 4CMenB into the routine immunization schedule.…”
Section: • • What Is Yet Unknown About 4cmenbmentioning
confidence: 99%
“…Between 2007 and 2012 a study carried out in two Italian regions found that 341 cases of IBDs of which 202 were of serogroup B . 5 In the same period in Italy the Istituto Superiore di Sanità (ISS, Italian National Health Institute) reported 991 cases IBDs, of which 455 were caused by serogroup B . 6 Overall, 81% of all cases of meningitis occurring during the first year of life are caused by serotype B , 6 and more than half occur in 4–8 months old infants.…”
Section: Introductionmentioning
confidence: 99%